Analysis of Crop Enterprise Combination among Small Holder Farmers in Delta North Agricultural Zone, Delta State, Nigeria - A. I. N, Kaine (Asian Journal of Agriculture and Rural Development, 2015)
This study on analysis of crop enterprise combination among small holder farmers was conducted in Delta North Agricultural Zone, Delta State, Nigeria. The study covered fifty farmers randomly selected from two villages randomly selected from five Local Government Areas in the study area. Frequencies, means, percentages and Net Profit Margin analysis was employed in analyzing the data obtained. Net farm income for two years was estimated and discussed. The result gave #277,269.47 and #214,020.30 for the year 2012 and 2013 respectively. The result showed that there was a sharp decline in output and income in the year 2013. The result also showed a drastic decline in both quantity and price of cassava, melon and tomato produced in the year 2013. Okro enterprise on the other hand showed a positive result at the end of 2013 farming year. The decline in output noticed among the various enterprise combinations may be attributed to some uncontrollable variables.